PENGARUH MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI SMA - . zulyadaini (Universitas Batanghari Jambi, 2017)
This research aims to know the influence of creative problem solving Instructional model to the mathematical problem solving ability of students in high school. The research method was experimental research with quasi-experimental design. independent variables used in this study is a creative problem solving Instructional model and direct instructional model. The dependent variable used is the mathematical problem solving ability. Determination of samples taken by random sampling technique with a sample of 78 consisting of 40 keas XI IPA 1 as experimental class and 38 class XI IPA 2 as a control class. The collection of data used mathematical problem solving ability test. the end of the analysis using the t test. The results showed that the value t (3.43) > ttable (1.665) mean H0 rejected or there are differences in mathematical problem solving ability of students that learned with creative problem solving Instructional model with the direct learning model. the difference is the mathematical problem solving ability of students that learned with creative problem solving Instructional model is higher than on mathematical problem solving ability of students that learned by direct Instructional model. Meaning that there are significant of the creative Problem Instructional model Solving mathematical problem solving ability of students. Keywords: Instructional model, creative problem solving Instructional model, direct instructional model, mathematical problem solving ability